Oxidation and dissolution behavior of UZr alloys for aqueous reprocessing applications. (February 2022) - Sreenivasulu, B.; Parida, Sanjit Kumar; Chandran, K.; Sriram, S.; Jena, Hrudananda; Rao, C.V.S. Brahmananda; Suresh, A.; Jayaraman, V.; Sivaraman, N.
Abstract: The oxidation behavior of sodium bonded U-6wt%Zr (UZr) alloys with clad T91 followed by their dissolution performance in nitric acid medium was investigated. At first dissolution behavior of UZr alloys were examined in HNO3 containing HF. Dissolution behavior of T91 clad was also examined under various conditions and found that its solubility increases with increasing HF concentration in HNO3 . The oxidation behavior of UZr alloy was examined in moist argon at 673 K and the solid phases formed during oxidation were identified as U3 O8 and U0.8 Zr0.2 O2 using powder XRD. Sodium bonding of UZr and T91 clad was simulated by heat-treatment of these materials at 823 K for a period of 400 h. The oxidation behavior of sodium bonded UZr-T91 samples were investigated at 623 K under flowing moist argon. The solid phases formed during the oxidation of sodium bonded UZr alloys were mainly composed of U3 O8, U0.8 Zr0.2 O2, NaUO3 and Na2 U2 O7 . In addition the bonded sodium was removed from UZr-T91 samples using induction heating (623 K) under dynamic vacuum (∼10 −5 torr) and their oxidation behavior was examined at 623 K in moist Ar and it was observed that only U3 O8 was formed during oxidation. The dissolution behavior of sodium bonded UZr-T91 clad samples (oxidised/non-oxidised) was subsequently examined in HNO3 medium for development of aqueous based reprocessing method for metal alloy fuel. The dissolution of U was found to be >99% in all the cases. Highlights: Oxidation behavior of UZr alloys in moist argon. Sodium bonding between UZr alloy and T91 clad by heat treatment at 823 K for 400 h. Oxidation behavior of sodium bonded and sodium distilled UZr-T91 samples. Dissolution behavior of T91 clad and UZr(oxidised/non-oxidised) samples in nitric acid medium.